2020
DOI: 10.7150/ijms.38914
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular Disorders and Oral Features in Systemic Lupus Erythematosus Patients: An Observational Study of Symptoms and Signs

Abstract: Aims: Systemic Lupus Erythematosus (SLE) is a connective tissue disease characterized by a wide range of pleomorphic pictures, including mucocutaneous, renal, musculoskeletal and neurological symptoms. It involves oral tissues, with hyposalivation, tooth decay, gingivitis, angular cheilitis, ulcers and glossitis. Temporomandibular disorders represent a heterogeneous group of inflammatory or degenerative diseases of the stomatognatic system, with algic and/or dysfunctional clinical features involving temporoman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
0
13
0
3
Order By: Relevance
“…Skin lesions are frequent, such as symmetric malar erythema, photo sensibility, hyperkeratosis, ecchymosis, oral or mucosal ulcerations, alopecia. Proteinuria or nephrotic syndrome, changes in urinary sediment, increase in serum creatinine and arterial hypertension are clinical manifestations of lupus nephritis [ 1 , 2 ]. SLE—Autoimmune prototype disease—is characterized by abnormal responses of T and B immune cells with excessive synthesis of autoantibodies and immune circulant complexes [ 3 ] associated with nonimmune factors [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Skin lesions are frequent, such as symmetric malar erythema, photo sensibility, hyperkeratosis, ecchymosis, oral or mucosal ulcerations, alopecia. Proteinuria or nephrotic syndrome, changes in urinary sediment, increase in serum creatinine and arterial hypertension are clinical manifestations of lupus nephritis [ 1 , 2 ]. SLE—Autoimmune prototype disease—is characterized by abnormal responses of T and B immune cells with excessive synthesis of autoantibodies and immune circulant complexes [ 3 ] associated with nonimmune factors [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the patient also had rheumatoid arthritis, therefore often experienced pain in the joints that existed throughout the body, including the TMJ. [ 13 14 ]As in the study of Aliko et al [ 6 ] showed the highest frequency of pain and joint sound found in patients with rheumatoid arthritis as much as 65% compared with the control group. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Among adults, the prevalence of TMD ranges from 1% to 75% for objective signs and 5% to 33% for subjective symptoms [ 4 ]. TMD’s etiology is multifactorial and often influenced by age, gender, hormonal imbalances, traumatic injuries, stress and other systemic diseases [ 3 , 5 , 6 , 7 ]. Age plays an etiological role in TMD: the prevalence of TMD is usually more common in young adults and the range from 20 to 40 years of age coincides with the peak of the incidence of TMD, as reported by previous studies [ 3 , 4 , 5 , 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%